The Social Construction of Colorblind Community in The Blind Side Movie by John Lee Hancock: A Discourse Analysis - Laksita Kumala Dewi; Rahayu Puji Haryanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research examines the representation and ideological construction of “Color Blindness” in the film The Blind Side, directed by John Lee Hancock, using Van Dijk’s Critical Discourse Analysis (CDA) approach. The purpose of this study is to answer three main questions: (a) how colorblindness is portrayed in story; (b) How is colorblind community constructed in the story; and (c) How does colorblind community socially construct a power relation in the story. The findings of the analysis demonstrate that The Blind Side not only tells an inspiring story of Michael Oher’s life change but also represents the narrative’s dominance from a white perspective and the inclination to simplify the complexities of racial relations. The portrayal of the Tuohy family as white saviors, as well as Michael Oher being held in stereotypes, subtly emphasizes racial hierarchy. In addition, the movie contains forms of prejudice camouflaged in positive tales, which overlook the context of systemic injustice.  This study adds to media studies by demonstrating how colorblind ideology in popular media may be a tool of symbolic domination, masking issues of racism and socioeconomic inequality. It emphasizes the importance of critical readings of media representations to understand their influence on social constructions of race, power, and identity.